PENGARUH PENGGUNAAN LARUTAN ALKALI DALAM KEKUATAN BENTUR DAN UJI DEGRADASI PADA KOMPOSIT TERMOPLASTIK BERPENGISI SERBUK SERABUT KELAPA - Harry Abrido S, Johannes Leonard S, Maulida (Universitas Sumatera Utara, 2012)
Composite is a combination of two different materials to obtain a material with physical properties and mechanical properties are better than any of its constituent parts. One of the many types of produced composite is composite with powdered natural fiber. This study uses the former polypropylene matrix derived from aqua cup and powdered coconut fiber as filler treated with Sodium Hydroxide (NaOH). The ratio of the matrix and the filler is 85:15. This ratio is the optimum value obtained by the composite tensile strength with some ratios are 100:0, 95:5, 90:10 and 85:15. The purpose of this study was to determine the effect of the use of an alkaline solution of the resulting composite properties such as impact strength, as well as the effect of degradation test on composite material former polypropylene with powdered coconut fiber as filler. Variation of composite degradation test were 10, 20 and 30 days, and immersion powder for 1 and 2 days. The method used in the manufacture of composites is the method of extrusion. The matrix form of the former polypropylene mixed with coconut fiber powder that has been soaked with NaOH, then mixed in a container, then put into the extruder operating temperature 1750C, printed using a hot press at a temperature of 1750C, and cut into pieces appropriate testing. The results showed that the optimum processing occurs with NaOH for 2 days. The test results showed degradation soaking for 2 days has impact strength values ​​higher than 1 day is equal to 0.086 J / mm at 10 days, 0.048 J / mm at 20 days and 0.052 J / mm at 30 days.Keywords : composite, former polypropylene, coconut fiber, NaOH, degradation test